2019
DOI: 10.1111/ajt.15363
|View full text |Cite
|
Sign up to set email alerts
|

Donor prone positioning protects lungs from injury during warm ischemia

Abstract: Abbreviations: CBCT, C-arm cone-beam computed tomography; cDCD, controlled donation after circulatory death; Cdyn, dynamic compliance; CSP, cold static preservation; Csta, static compliance; DBD, donation after brain death; ELISA, enzyme-linked immunosorbent assay; EVLP, ex vivo lung perfusion; IL, interleukin; PawP, peak airway pressure; PEEP, positive end-expiratory pressure; Pplat, airway plateau pressure; PVR, pulmonary vascular resistance; TUNEL, terminal deoxynucleotidyl transferase deoxyuridine triphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…After 3 hours of WIT, 6 hours of cold preservation and 6 hours of normothermic machine perfusion, the results show a better tolerance to WIT, less atelectasis and apoptosis in the prone positioned group. These results confirmed once again the importance of ventilation in lung preservation (8). Great interest has always been given to the intrapulmonary thrombi formation after lung procurement from DCD and subsequent reperfusion injury.…”
Section: Pre-clinical Experiencessupporting
confidence: 68%
“…After 3 hours of WIT, 6 hours of cold preservation and 6 hours of normothermic machine perfusion, the results show a better tolerance to WIT, less atelectasis and apoptosis in the prone positioned group. These results confirmed once again the importance of ventilation in lung preservation (8). Great interest has always been given to the intrapulmonary thrombi formation after lung procurement from DCD and subsequent reperfusion injury.…”
Section: Pre-clinical Experiencessupporting
confidence: 68%
“…To that end, we recently modified our protocol to allow for lung inflation 15 minutes after death declaration. We also adopted the measure of proning donors early after death as this maneuver has demonstrated marked benefits in a preclinical translational DCD model . Our recent preliminary data are promising, but the real impact of these maneuvers in increasing lung utilization is still to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Prone positioning has shown beneficial effects for patients with lung injury (83). Prone positioning also improved graft function in a pig DCD EVLP model (84). Niikawa et al tested the role of prone positioning of lungs on EVLP and demonstrated better oxygenation and lung compliance, lower weight ratio, and lower IL-1β levels in prone position lungs compared to control lungs in supine position (67).…”
Section: Prone Positioningmentioning
confidence: 99%